Analysis of Corporate Culture Imple-Mentation Strategi of Bank Sumut Sharia Business Unit During the Covd-19 An-Deeemic N An Islamic Perspective - Rizki Amalia Tanjung; Mustapa Khamal Rokan (Penerbit Jurnal Indonesia, 2022)
In general, corporate culture is an opportunity to expand or train human resources with changes in atti-tudes and behaviors such as beliefs, values and norms that characterize the company followed by compa-ny members and are expected to be in harmony with the obstacles that arise and come. In the Sharia Business Unit of Bank Sumut there is a corporate culture whose best company values, vision, mission and motto of the company based on an Islamic perspective. However, during the Covid-19 pandemic , there are some values of companies whose implementation is less effective as usual, namely Energetic, Friendly, High Integrity and Safe. This research aims to identify the principles of corporate culture, cor-porate culture in an Islamic perspective and strategy to implement corporate culture during the Covid-19 pandemic in bank Sumut's Sharia Business Unit. In this study, the researchers used descriptive qualitative study techniques. The method of data collection is to use observation, interviews and documentation. The results of the study concluded that the principles of corporate culture in the Sharia Business Unit of Bank Sumut are the company's first value that is short with BEST, vision, mission and company motto. Second, the corporate culture of Bank Sumut's Sharia Business Unit is based on an Islamic perspective. Third, to overcome problems in several company values that encountered obstacles during the Covid-19 period , the company carried out a project to implement the corporate culture of Bank Sumut's Sharia Business Unit during the Covid-19 period.